Combining GWAS, Genome-Wide Domestication and a Transcriptomic Analysis Reveals the Loci and Natural Alleles of Salt Tolerance in Rice (Oryza sativa L.) - Lv, Yang; Ma, Jie; Wei, Hua; Xiao, Fang; Wang, Yueying; Jahan, Noushin; Hazman, Mohamed; Qian, Qian; Shang, Lianguang; Guo, Longbiao (Frontiers in Plant Science, 2022)
Soil salinity is a serious threat to rice productivity sustainability worldwide, accordingly, detecting loci and natural alleles for salt tolerance to accelerate rice improvement and yield the resilient production varieties is necessary for ensuring future harvests. In this study, a set of 191 mini-core population, collected from different regions around the world, were evaluated the salt-tolerance based on the phenotypes of rice plant growth and development at seedling stage, and divided standard evaluation score (SES) of visual salt injury into five different grades. Based on ~3.17 million single nucleotide polymorphisms (SNPs), a total of 155 significantly-associated SNPs and 275 salt sensitivity-related candidate genes were identified by a genome-wide association study (GWAS) of SES. To further explore salt sensitivity-related predicted salt tolerant genes and allelic diversity, we performed haplotype analysis, genome-wide domestication detection, and transcriptome analysis for breeding improved varieties. The presented data and genetic resources seem valuable for providing genes involved in salt-tolerance genotypes.